2021
DOI: 10.1002/smll.202105775
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Interfacial Engineering of MoS2‐Modified Zn Single‐Atom Catalysts for Efficient Osteomyelitis Sonodynamic Ion Therapy

Abstract: sepsis. Nearly 40% Patients suffered from bone infection have the risk of recurrence and chronic infection. [3] Clinical treatments for osteomyelitis involve the long-term and high-dose antibiotics administration, as well as multiple surgical debridement. [4] However, the notable problems of these approaches are obvious. The overuse of antibiotics not only brings severe side effects, but also causes drug-resistant. [5] The removed bone tissue by debridement will weaken the musculoskeletal support and lead to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 38 publications
0
38
0
1
Order By: Relevance
“…Several studies have found that SDT had significant bactericidal activity against bacterial infections, and even methicillin-resistant Staphylococcus aureus ( Yu et al, 2021 ). Meanwhile, as PDT is limited by the inability of light to penetrate through human tissue, SDT that could overcome this limitation, exhibit great potential to address the problem of deep tissue bacterial infection such as osteomyelitis, otitis media, and periprosthetic infection ( Su et al, 2020 ; Feng et al, 2022 ; Su et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that SDT had significant bactericidal activity against bacterial infections, and even methicillin-resistant Staphylococcus aureus ( Yu et al, 2021 ). Meanwhile, as PDT is limited by the inability of light to penetrate through human tissue, SDT that could overcome this limitation, exhibit great potential to address the problem of deep tissue bacterial infection such as osteomyelitis, otitis media, and periprosthetic infection ( Su et al, 2020 ; Feng et al, 2022 ; Su et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…312 As a consequence, it is urgent to develop superior single-atom sonocatalysts for the treatment of osteomyelitis. To this end, Feng et al 297 recently developed a bi-functional sonosensitizer, Zn-SACs, for treating osteomyelitis through sonodynamic therapy and the osteoinductive ability of Zn 2+ (Fig. 17e–h).…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…It is estimated 700,000 people a year die of drug-resistant bacteria infections [41][42][43]. In this case, it is important to develop novel materials for treating infections [44,45]. Recently, SACs/SANs have shown great potential in fighting against the infection (Table 1).…”
Section: Applications Of Sans In the Treatment Of Infectionmentioning
confidence: 99%